Safe and radiation-proof observation glass from multi-component borotellurite glass / M. M. Naaim and R. Hisam - Naaim, M.M.; Hisam, R. (2022)
In this work, 15B2O3-60TeO2-11Bi2O3-10Li2O-1Ho2O3-3Yb2O3 glass sample was synthesized by using the melt-quenching technique. The density test applies the Archimedes’ principle and obtained 5297.5 kg/m3 which may be attributed by the presence of heavy elements in the glass sample. The radiation shielding properties such as mean free path (MFP) and half-value layer (HVL) were investigated by using the Phy/X-PSD software. The values obtained were relatively better than typical radiation-shielding glasses. The improvement that occurred in the radiation shielding parameters may be contributed to the high-density value of the glass sample and therefore, potentially be the alternative to a transparent observation glass for radiation shielding purposes.